INTELLIGENCE ANALYSIS IN DETECTING THE POTENTIAL FOR SOCIAL CONFLICT IN PAREPARE CITY (CASE STUDY: THE DEVELOPMENT OF GAMALIEL CHRISTIAN SCHOOL) - Latif, Asriyadi; Sunardi Purwanda; Muhammad Sabir; Aksah Kasim; Kairuddin (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
This study examines the role of police intelligence analysis in the early detection of potential socio-religious conflict, using the construction of Gamaliel Christian School in Parepare City as a case study. Employing a normative–empirical legal research method, the study analyzes relevant statutory regulations alongside empirical data obtained through interviews, observations, and document analysis conducted at the Intelligence and Security Unit (Satintelkam) of the Parepare Police. The findings reveal that the development project reflects a latent socio-religious conflict characterized by community resistance, religious identity sensitivity, and the politicization of development issues. The conflict was not solely driven by administrative or licensing disputes but was largely influenced by perceptions of injustice, social exclusion, and weak inclusive social communication. The study further finds that Satintelkam plays a strategic role in early conflict detection through information gathering, vulnerability mapping, and social engagement.  However, the effectiveness of intelligence analysis remains constrained by limited cross-sectoral integration, insufficient utilization of intelligence assessments in local policymaking, and the lack of data-driven social intelligence approaches. This research contributes to the development of police intelligence studies by highlighting the importance of intelligence-based early warning systems and offering policy-oriented insights for sustainable socio-religious conflict prevention at the local level.